Comparative study of single-port single-channel and single-port multi-channel adrenalectomy in various maximum tumor diameters - Pengcheng Zhang; Yuhan Pei; Yunlai Zhi; Fanghu Sun; Ninghong Song (BMC Surgery)
Abstract Background Investigating the application of single-port single-channel and single-port multi-channel adrenalectomy in various maximum tumor diameters. Methods Retrospective analysis of clinical data from 218 adrenal tumors treated with single-port retroperitoneoscopic adrenalectomy at Lianyungang Clinical Medical College of Nanjing Medical University from September 2018 to November 2023. All adrenal tumors are benign lesions classified as T1 stage. Tumors were classified into three groups based on their maximum diameter: ≤3 cm (Group A), >3 cm and ≤ 4 cm (Group B), and > 4 cm and ≤ 5 cm (Group C). Based on the surgical approach, patients were divided into single-port single-channel and single-port multi-channel groups. Group A had an average tumor diameter of (2.32 ± 0.45) cm with 46 single-port single-channel and 53 single-port multi-channel cases; Group B had (3.42 ± 0.31) cm with 33 single-port single-channel and 45 single-port multi-channel cases; Group C had (4.60 ± 0.28) cm with 18 single-port single-channel and 23 single-port multi-channel cases. Comparisons were made between single-port single-channel and single-port multi-channel groups in terms of operation time, hospital stay, intraoperative bleeding, postoperative pain score, surgical complications, incision length (total length of all incisions), and the need for additional puncture holes for each tumor size group. Results All 218 surgeries were successfully completed without conversion to open surgery. In Group A, no significant difference was observed between single-channel and multi-channel groups in terms of operation time and blood loss (P > 0.05), but significant differences were found in hospital stay, pain score, subcutaneous emphysema incidence, and incision length (P < 0.05). In Group B, there was no significant difference between single-channel and multi-channel groups regarding operation time and blood loss (P > 0.05), but significant differences were observed in hospital stay, pain score, subcutaneous emphysema incidence, and incision length (P < 0.05). In Group C, no significant difference was observed between single-channel and multi-channel groups in terms of hospital stay, blood loss, pain score, incision length, vascular injury, and subcutaneous emphysema incidence (P > 0.05), but significant differences were found in operation time and the incidence of additional puncture holes (P < 0.05). Postoperative follow-up ranged from 4 to 22 months, with an average of 11.5 months, and no complications were observed. Conclusions Single-port single-channel laparoscopy has significant advantages in surgeries for tumors with a maximum diameter ≤ 4 cm, as it can directly reach the target organ, reduce separation operations, cause less damage, and has good cosmetic effects. For adrenal tumor surgeries with a maximum diameter > 4 cm, the multi-channel technique is superior to the single-channel technique in terms of shorter hospital stay and the need for additional punctures.